Significant prevalence of sickle cell disease in Southwest Germany: results from a birth cohort study indicate the necessity for newborn screening - Kunz, Joachim; Awad, Saida Beatrix; Happich, Margit; Muckenthaler, Lena; Lindner, Martin; Gramer, Gwendolyn; Okun, Jürgen G.; Hoffmann, Georg F.; Bruckner, Thomas; Muckenthaler, Martina; Kulozik, Andreas (Annals of hematology, 2016)
Children with sickle cell disease (SCD) benefit from newborn screening, because life-threatening complications can be prevented by pre-symptomatic diagnosis. In Germany, the immigration of people from endemic countries is steadily growing. Comprehensive data about the epidemiology and prevalence of SCD in Germany are however lacking, and SCD is not included in the national newborn screening program. We provide data on the prevalence of SCD in a population from both urban and rural areas in Southwest Germany.